2014
DOI: 10.1002/micr.22334
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of flap growth and long‐term results of pediatric mandible reconstructions using free fibular flaps

Abstract: Currently, the free fibular flap is well accepted as the first choice for mandibular reconstruction. Achieving functional results in pediatric patients requires a different approach than that employed for mature patients. Because the pediatric craniofacial skeleton continues to grow, reconstruction is more challenging, and the long-term results can be different from those of adult patients. In this study, we sought to measure flap growth objectively in our series. Ten pediatric patients who underwent reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 38 publications
(60 reference statements)
1
44
0
Order By: Relevance
“…As a result, some patients eventually required orthognathic surgery or the transfer of new flaps for surgical correction as they grew. On the contrary, most series on pediatric head and neck reconstruction have reported that free flaps seem to grow commensurately with surrounding structures . We reviewed a series of 51 patients < 18 years of age who underwent mandibular reconstruction with vascularized fibula flaps from 15 articles; we found that the number of patients with preserved growth potential was greater than those with no growth potential and concluded that the growth potential of the fibula was related to age, condylar preservation, tumor pathology, and postoperative radiotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, some patients eventually required orthognathic surgery or the transfer of new flaps for surgical correction as they grew. On the contrary, most series on pediatric head and neck reconstruction have reported that free flaps seem to grow commensurately with surrounding structures . We reviewed a series of 51 patients < 18 years of age who underwent mandibular reconstruction with vascularized fibula flaps from 15 articles; we found that the number of patients with preserved growth potential was greater than those with no growth potential and concluded that the growth potential of the fibula was related to age, condylar preservation, tumor pathology, and postoperative radiotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, most series on pediatric head and neck reconstruction have reported that free flaps seem to grow commensurately with surrounding structures. 4,19,22,47,48 We reviewed a series of 51 patients < 18 years of age who underwent mandibular reconstruction with vascularized fibula flaps from 15 articles; we found that the number of patients with preserved growth potential was greater than those with no growth potential and concluded that the growth potential of the fibula was related to age, condylar preservation, tumor pathology, and postoperative radiotherapy. This systematic review showed that whereas reconstruction after benign lesion resection, reconstruction between 8 and 12 years of age (which was termed the rapid growth stage), and condylar preservation facilitate postoperative mandibular growth, postoperative radiotherapy inhibits the same.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the continuous growth of the fibula and mandible, free fibula flap reconstruction of the mandible in pediatric patients has been shown to be effective, with minimal postoperative cross bite complications [6]. In adults, the use of 3D CAD/CAM technology in free fibula flap reconstructions have decreased operative time and increased accuracy [3e5, 20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of the FVFG in children has progressively gained popularity for mandibular reconstructions of large oncological resections and severe facial deformities of the lower jaw. 1,2,5 Despite its advantages, the FVFG handicaps result from the reduced height of the fibula ($10 mm), which is suboptimal for achieving a simultaneous reconstruction of the facial contour and alveolar height. 4 Several technical modifications and secondary procedures have been described to overcome the limitations of the FVFG in terms of bone height such as double-barrel designs and vertical distraction, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the use of FVFGs for pediatric mandibular reconstruction without associated ankle morbidity. 1,2,5 However, most of these remain short series of patients with limited follow-up. Moreover, Sulaiman et al evaluated the long-term effects on the foot and ankle following FVFGs in children and concluded that resecting the fibula, even with preservation of a 6-cm distal fibular stump, may lead to abnormal growth in children younger than 6 years old.…”
Section: Discussionmentioning
confidence: 99%